[AR] Mawqif al-Nuhah al-Kufiyyin min Wad' al-Mustalahat al-Nahwiyyah al-Jadidah: The Position of Kufic Grammarians Regarding the Development of New Grammatical Terms (Afaq Lughawiyyah, 2024)
The Kufic ??grammarians were the most focused on studying Qur’anic verses and hadiths. Accordingly, they built a special curriculum that influenced their grammatical directions, which led to the development of new grammatical terms. There is very little study on Kufic grammar, and the focus on Kufic grammatical terms was the least, and it did not receive comprehensive attention from scholars except for some attempts that were not completed, and this is due to the scarcity of sources and the difficulty of accessing them. Therefore, this qualitative research aims to highlight these Kufic terms, while identifying the position of Kufic grammarians regarding their status, by following two methods: The first of them is a descriptive method, in which it studies a sample of these terms in a linguistic and semantic way and lists the corresponding terms of visual grammar and their equivalents (i.e., pure Kufic terms). The second is an analytical method, which shows their point of view through the development of grammatical terms. The researcher organizes a special table of grammatical terms from two schools: Kufa and Basra, which he collected from important references. Through this research, it became clear that the Kufic grammarians create a few new grammatical terms, which distinguish them from the Basra grammarians. The terms also indicate their superior status and ability in the field of Arabic grammar.